Thin-walled composite tubes using fillers subjected to quasistatic axial compression - Al-Qrimli H.F.; Mahdi F.A.; Ismail F.B.; Alzorqi I.S. (Institute of Physics Publishing, 2023)
Automotive industry; Crashworthiness; Crushing; Energy absorption; Fillers; Glass industry; Loads (forces); Palm oil; Thin walled structures; Tubes (components); Wood; Wood products; Crashworthiness parameters; Different geometry; Material characterizations; Maximum crushing loads; Quasi-static loads; Quasistatic axial compression; Specific energy absorption; Thin-walled composites; Engineering education; Composites; Compression; Fillers; Samples; Tubes